THE CLERGY SEXUAL ABUSE CRISIS AND THE CHURCH IN THE PHILIPPINES - McTavish, James (Asian Horizons, 2020)
At a global level, much valuable research has been published on clerical sexual abuse in the Catholic church. Critical insights gained have highlighted the extent of the problem, and assisted the overall efforts to provide healing to victims. Pope Francis has been particularly active in encouraging the whole Church to confront the issue, and seek for much needed healing remedies. In the Asian context, the issue of clerical sex abuse is rarely approached. This is in line with a general continental avoidance of discussions in any way connected to problems regarding sexuality. This essay will first review some general considerations of clerical sexual abuse on the global scale before looking more closely at the issue in the context of the Catholic Church in the Philippines. Whilst some progress has been made in the Philippines setting, efforts are largely stifled by the cultural taboo of speaking out, the shame of revealing such episodes, the high esteem shown to the Clergy, and the reticence of the Church to vigorously investigate and pursue any such allegations. The recent legislation of Pope Francis (Vos estis lux mundi), which makes reporting of clerical sexual abuse mandatory, could hopefully go some way in encouraging the Church in Asia to respond more adequately in its mission of protecting minors and vulnerable adults.